Perceived Norms for Drinking in the Transition From High School to College and Beyond - Stappenbeck, Cynthia A. (Rutgers University, 2010)
OBJECTIVE: We evaluated selection and socialization processes associated with perceived descriptive norms and drinking from high school through the first 2 years of college. METHOD: Participants (n = 2,247; 61.6% female) completed measures of high school drinking and descriptive drinking norms for their social group and the typical student at the university they were entering, as well as alcohol use and social-group norms through their sophomore year of college. We conducted structural equation models by gender and ethnicity to test high school drinking and drinking norms as predictors of collegiate drinking and social-group norms. RESULTS: Perceptions of typical-college-student drinking during high school predicted freshman-year drinking for men but not women and for White but not Asian or Hispanic students. High school social-group norms predicted freshman drinking for White but not Asian or Hispanic students, whereas freshman social-group norms predicted sophomore drinking for all participants. CONCLUSIONS: Selection and socialization processes co-occur during this transitional time. Heavy drinkers in high school who perceive their friends to be heavy drinkers select into college social groups with perceived heavy drinking. Men and White students who perceive heavy drinking by the typical college student tend to drink heavily in college and choose social groups with perceived heavy drinking. These results support the importance of interventions that are tailored to the individual and that target perceptions of typical-college-student and social-group drinking before entering college for Whites and men but after matriculation for women, Asian, and Hispanic students.